Circles. A, The birth of an entrepreneurial initiative - Mendonca, Valerie, (SAGE Business cases., 2024)
This case describes the entrepreneurial journey of two college friends-Anchal Taatya and Abhiram Nukalapati. While studying together at IIM Ahmedabad, they saw an opportunity for aggregating credit card discounts and launched a pilot in February 2019 under the name Circles. Circles helped discount seekers and credit card holders to connect and make transactions. The Case A outlines their journey until the launch, where they face the dilemma of building a Business-to-Business (B2B) product or a Business-to-Customer (B2C) product. The Case B outlines their struggles in building a B2C version and eventual shutdown of the venture. The key objective of discussing this case is to understand the business formation stages of a college start-up, and how they arrived at opportunity identification. The case is aimed at enabling classroom discussions on the role of trust in platform businesses and how regulations-or lack thereof-can shape the destiny of new ventures.